A semi-quantitative deformation model for pore formation in isotactic polypropylene microporous membrane. (2nd December 2015) - Lin, Yuanfei; Meng, Lingpu; Wu, Lihui; Li, Xueyu; Chen, Xiaowei; Zhang, Qianlei; Zhang, Rui; Zhang, Wenhua; Li, Liangbin
Abstract: Aiming to unveil the key structures and processing parameters of precursor film for the micropore formation, the structure and mechanical behavior of isotactic polypropylene (iPP) casting films prepared at different processing conditions are systematically studied with small and wide angle X-ray scattering measurements as well as tensile analysis. Draw ratio and cast roll temperature are found to be the key processing parameters, which determine orientation of lamellar stack and thickness of lamellar as well as amorphous layers, respectively. Furthermore, these two important structural parameters, the orientation of lamellar stack and the thickness of amorphous layer, show positive correlations with the formation of micropores. Considering coupling effects of tight folds and lamellar-fibrillar or lamellar-amorphous transformation, a semi-quantitative deformation model for the micropore formation is proposed to correlate surface porosity and elastic recovery rate with structural parameters of precursor film. Graphical abstract: Highlights: A semi-quantitative model is proposed to explain structure-porosity or ER relation. Lamellar-fibrillar transformation in pore formation affects porosity positively. Key structure and processing parameters of precursor film on porosity are unveiled. Orientation parameter and amorphous thickness determine porosity positively. Draw ratio and cast roll temperature are key processing parameters for micropores.